NEED ANALYSIS OF AUGMENTED REALITY-BASED CHEMISTRY LEARNING MEDIA IN TORAJA UTARA REGENCY - Tiara Lestari Paembonan; Varisky Abraham Dumanaw; Dominikus Rojoki Manullang; Yustinus Tarigan; Lidia Aprileny Hutahaean (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This descriptive research aims to identify the learning styles of grade 11 high school students in science major on chemistry learning and measure the level of optimization of teachers and students regarding the use of Augmented Reality-based chemistry learning media. This research was conducted on 9 chemistry teachers and 90 students majoring in science in Toraja Utara Regency. Data collection has been done using a closed-ended questionnaire with 4 choices consisting of 25 statements for chemistry teachers and 18 statements for science major students. The data were analyzed using a percentage formula and the results obtained showed that teachers had not optimized the use of Augmented Reality as a chemistry learning media. Furthermore, the most common learning style of students is visual, followed by kinesthetic and then auditory